Impaired learning of predators and lower prey survival under elevated CO2: a consequence of neurotransmitter interference. (14th September 2013) - Chivers, Douglas P.; McCormick, Mark I.; Nilsson, Göran E.; Munday, Philip L.; Watson, Sue‐Ann; Meekan, Mark G.; Mitchell, Matthew D.; Corkill, Katherine C.; Ferrari, Maud C. O.
Abstract Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO2 was reversed when fish were treated with gabazine, an antagonist of the GABA‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO2, as a result of impaired learning, could have a major influence on population recruitment.